Multienvironment Testing for Trait Stability and G × E Interaction on N2 Fixation, Plant Development, and Water-Use Efficiency of 21 Elite Groundnut (Arachis hypogaea L.) Genotypes in the Guinea Savanna - Oteng-Frimpong, Richard; Dakora, Felix D. (Frontiers in Plant Science, 2019)
Groundnut production constitutes an integral part of the livelihoods of the people in the Guinea savanna of West Africa. This region accounts for over 70% of the total groundnut production in Ghana, 90% in Nigeria, and virtually 100% in Mali and Burkina Faso. However, harsh environmental conditions often result in drastic yield reductions. In this study, we identified groundnut genotypes with superior symbiotic efficiency, greater pod yield and plant water-use efficiency from 21 advanced groundnut breeding lines from ICRISAT after testing them at three locations in the Guinea savanna of Ghana over two consecutive year. Average N contribution by the groundnut genotypes ranged from 48 to 108 kg N ha-1, and mean pod yield from 0.58 to 2.1 t ha-1. Genotype ICGV-IS 08837 produced about 2.5-fold more pods than CHINESE which was the most widely cultivated variety by farmers. Of the 21 genotypes studied, ICGV 99247 recorded the highest shoot δ13C value and hence superior water-use efficiency, which was consistent with stability estimates and mean performance. We also measured the G x E influence on pod yield, N-fixed, shoot δ13C, and mega-environments for testing groundnut in the Guinea savanna, and these were all significant, although the effect was minimal on shoot δ13C values. Of the locations studied, Nyankpala and Damongo were more discriminating and each constituted a mega-environment for conducting future groundnut trials in the Guinea savanna. ICG 6222 emerged as the best cultivar for the Damongo mega-environment, while ICGV-IS 08837 was the best genotype for the Nyankpala mega-environment. The genotypes exhibiting the highest sensitivity of N2 fixation to the environment included ICG 6222, ICGV 00068 and ICGV 03315 (bi > 1.3), while Pi estimates ranked genotypes ICG 6222, ICGV 03315 and ICGV-IS 08837 as the best groundnut cultivars in symbiotic N contribution. From this study, genotypes ICGV-IS 08837, ICG 6222, ICGV 03315 and ICGV 00068, which ranked tops for overall pod yield, shoot biomass production and amount of N-fixed, were the most suitable candidates to recommend for use in developing new varieties for this part of the Guinea savanna.